1976
DOI: 10.1677/joe.0.0680257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cortisol on Utilization and Hepatic Release of Glucose in the Marsupial Brush-Tailed Opossum, Trichosurus Vulpecula

Abstract: Brush-tailed opossums were prepared surgically with indwelling heatic and jugular venous catheters for blood sampling without disturbance in the conscious state. Hepatic extraction of Rose Bengal was 21 +3 (s.d.) % and hepatic clearance, used as a measure of hepatic blood flow, was 42.5 +7 ml/kg/min. Hepatic relaease of new glucose, calculated from the thorias vena caval-hepatic venous difference in glucose specific activity at equilibrium during i.v. infusion of [14C]glucose and hepatic blood flow, was 3.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Laboratory studies with a number of species of macropods have shown that they are resistant to the usual nitrogen-mobilising diabetogenic effect of the steroid hormone cortisol (Griffiths et al 1969;McDonald and Bradshaw 1981). This is not a general marsupial characteristic, however, as cortisol injections increase nitrogen excretion and elevate blood glucose levels in brush-tailed possums (Trichosurus vulpecula) (McDonald and Than 1976;McDonald 1977). Cortisol is a catabolic steroid released in response to stressors, such as starvation, and stimulates gluconeogenesis through the breakdown of tissue protein with the release of nitrogen that is normally excreted.…”
Section: Seasonal Deficiencies Of Nitrogen Phosphorus and Energymentioning
confidence: 99%
“…Laboratory studies with a number of species of macropods have shown that they are resistant to the usual nitrogen-mobilising diabetogenic effect of the steroid hormone cortisol (Griffiths et al 1969;McDonald and Bradshaw 1981). This is not a general marsupial characteristic, however, as cortisol injections increase nitrogen excretion and elevate blood glucose levels in brush-tailed possums (Trichosurus vulpecula) (McDonald and Than 1976;McDonald 1977). Cortisol is a catabolic steroid released in response to stressors, such as starvation, and stimulates gluconeogenesis through the breakdown of tissue protein with the release of nitrogen that is normally excreted.…”
Section: Seasonal Deficiencies Of Nitrogen Phosphorus and Energymentioning
confidence: 99%
“…INTRODUCTION Although there is a general similarity between adreno¬ cortical functions in the marsupials so far investigated and those of the eutherian mammals, some species of marsupials exhibit unusual features (McDonald, 1977). In the most investigated species of marsupial, the brush-tailed possum Trichosurus vulpécula, a member of the family Phalangeridae, the metabolic actions of glucocorticoids, within the physiological range of plasma concentration, closely resemble those in eutherian mammals (Than & McDonald, I914a,b;McDonald & Than, 1976). In contrast, some members of the large family of kangaroos and wallabies (Macropodidae), the red kangaroo Macropus rufus and the quokka Setonix brachyurus, appear to be highly resistant to their diabetogenic and nitrogenmobilizing actions (Griffiths, Mclntosh & Leckie, 1969;McDonald & Bradshaw, 1981).…”
mentioning
confidence: 99%